2017
DOI: 10.2214/ajr.16.17578
|View full text |Cite
|
Sign up to set email alerts
|

Sports-Related Groin Pain Secondary to Symphysis Pubis Disorders: Correlation Between MRI Findings and Outcome After Fluoroscopy-Guided Injection of Steroid and Local Anesthetic

Abstract: Fluoroscopy-guided corticosteroid symphyseal injection is a safe and effective treatment of sports-related groin pain. It is more frequently associated with a complete recovery in patients who display an isolated superior cleft sign on MRI. MRI not only is useful in characterizing groin injuries but also may be helpful in predicting response to therapeutic injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…The medial head inserts at the pubic crest and fuses with the articular capsule; its lateral head is close to the external inguinal foramen and attaches more laterally and fuses with the adductor longus. 5,[32][33][34][35][36] The prepubic plate represents the central axis connecting the anterior abdominal wall and the lower extremities and is a dynamic stabilizer. It has two layers that are formed by the aponeurosis of the external oblique muscle and by fibers of the adductors.…”
Section: Deep Subgluteal Syndromementioning
confidence: 99%
See 4 more Smart Citations
“…The medial head inserts at the pubic crest and fuses with the articular capsule; its lateral head is close to the external inguinal foramen and attaches more laterally and fuses with the adductor longus. 5,[32][33][34][35][36] The prepubic plate represents the central axis connecting the anterior abdominal wall and the lower extremities and is a dynamic stabilizer. It has two layers that are formed by the aponeurosis of the external oblique muscle and by fibers of the adductors.…”
Section: Deep Subgluteal Syndromementioning
confidence: 99%
“…Recent studies demonstrated strong connections with the anterior pubic ligament, introducing the concept of the pyramidal-pubic anterior ligament-adductor longus complex. [32][33][34][35][36] A dedicated athletic pubalgia protocol is recommended for this specific subset of injury. The patient is imaged supine.…”
Section: Deep Subgluteal Syndromementioning
confidence: 99%
See 3 more Smart Citations